EFEKIVITAS MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DESA DI DESA PULAU KOMANG KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2016 - Andesko Rivaldi; Ahmad Tarmizi Yusa (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
This research was conducted in Pulau Komang Village, Sentajo Raya District, Kuantan Singingi Regency. The purpose of this study was to determine the effectiveness of the Village Development Planning Meeting (Musrenbang) in Pulau Komang Village, Sentajo Raya District, Kuantan Singingi Regency in 2016. The usefulness of this study is also expected to be an input for Pulau Komang Village regarding the implementation of Village Development Planning Consultations, and also expected to be useful to increase knowledge and can be a reference for further research with the same subject matter. With the aim of knowing and explaining the Effectiveness of Village Development Planning Consultation in Pulau Komang Village. In line with the purpose of this study, the population and sample in this study were the Village Heads of Pulau Komang, the Village Commands of Pulau Komang amounted to 3 people, the Village Consultative Body of Pulau Komang as many as 3 people and the Community Shop of Village Pulau Komang as many as 5 people. The sampling technique used is the Slovin formula cited by Danang Sunyoto (20013; 16), and the theory I use is a theory from Permendagri Number 66 of 2007, with indicators set as many as 3 indicators. After all data were analyzed with quantitative and qualitative research, the results of research on the effectiveness of Village Development Planning (Musrenbang) in Pulau Komang Village, Sentajo Raya District, Kuantan Singingi Regency in 2016 were included in the category of "Effective Enough"..